Analysing the perception and usage of local textile prints a study of koforidua technical university (International Journal of Scientific Research and Management (IJSRM), 2018)
People all over the world portray different attitudes towards the same stimuli. This is because individuals have different perceptions about a particular stimulus. Obviously, consumer perception and attitudes towards their own country’s products keeps on changing. Personal observations and empirical evidence shows that Ghanaian textile industry have not been able to achieve its set objectives due to inappropriate product marketing and this has influenced the perceptions people greatly towards the Ghanaian prints. The aim of the study is to determine what is responsible for the perceptions towards made-in-Ghana textiles and to ascertain what can be done to influence the perception towards the Ghanaian textiles. The sample size consisted of two hundred [200] respondents mainly from selected staff and students of Koforidua Technical University. Both primary data and secondary data and interviews and questionnaires to gather the relevant data needed for the research were used. Statistical tools such as tables and bar graphs were used for the analysis. The study revealed that students of Koforidua Technical University are generally satisfied with made-in-Ghana textiles but had some dissatisfaction with the prices of these textiles. The study suggested that the Ghana textile industry should make their products more price competitive to encourage sales increase and to discourage the influx of the local designs from foreign markets into the country.